2016
DOI: 10.5152/balkanmedj.2016.15701
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Its Impact on Mental Fatigue in Patients with Mild Traumatic Brain Injury

Abstract: Background: Although mental fatigue was well-recognized as one of the long-term consequences following mild traumatic brain injury (MTBI) that required ongoing support, evidences for the optimal management remained inadequate. Aims: To investigate the temporal profile of mental fatigue during the first year after MTBI and examine the impact of perceived social support on the recovery from post-MTBI fatigue. Study Design: Observational case-control study. Methods: This study was conducted among post-MTBI patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…This might have an association with the general use of social media which has to be followed in further research. However, it has been known that patients suffering from a mild brain injury show a lower occurrence of mental fatigue symptoms when perceiving social support [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might have an association with the general use of social media which has to be followed in further research. However, it has been known that patients suffering from a mild brain injury show a lower occurrence of mental fatigue symptoms when perceiving social support [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean total score ranges from 1 to 7, where a higher score denotes more perceived social support. The MSPSS has shown good psychometric properties [ 40 ], and it has been used in TBI patients [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…A social history is also critically important to determine how a patient's habits and social support structure might impact recovery. For example, it has been reported that perceived social support [117] and early return to exercise [118] may be salutary after mild TBI, while TBI may be a risk factor for problem gambling [119] and alcohol abuse [120]. A history of TBI is significantly more prevalent among the homeless [121] and poor [122].…”
Section: Medications and Social Historymentioning
confidence: 99%